2022
DOI: 10.1101/2022.04.01.22273317
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparative analysis of depression between pregnant and non-pregnant adolescents in a southwestern town in Nigeria

Abstract: Background: Adolescence constitutes a risk factor for mental health problems, and this may be further complicated by pregnancy . The rate of adolescent pregnancy is still extremely high in the sub-Saharan Africa including Nigeria .  Pregnancy and mental health problems during adolescence constitute double vulnerability for negative outcomes for the adolescents and their offspring .   Methodology: The study design was cross-sectional, and it was conducted in Osogbo metropolis, Osun State, Southwest, Nigeria. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…In a study conducted in Yaoundé Cameroon on a sample of 1,307 participants, 70% of perinatal teenagers had depression of varying severity [13]. A comparative analysis study of depression in pregnant and non-pregnant adolescents found that the prevalence of depression among pregnant adolescents was two folds higher than the nonpregnant adolescent population [14]. The result of the study indicated a relationship between pregnancy status and mental disorders like depression and anxiety among the teenage girls.…”
Section: Introductionmentioning
confidence: 93%
“…In a study conducted in Yaoundé Cameroon on a sample of 1,307 participants, 70% of perinatal teenagers had depression of varying severity [13]. A comparative analysis study of depression in pregnant and non-pregnant adolescents found that the prevalence of depression among pregnant adolescents was two folds higher than the nonpregnant adolescent population [14]. The result of the study indicated a relationship between pregnancy status and mental disorders like depression and anxiety among the teenage girls.…”
Section: Introductionmentioning
confidence: 93%